Optical Properties of Transition Metal Dichalco-genide Monolayers in the vicinity of Noble Metal Surfaces - Trnjanin, Nermin (My University, 2019)
In recent years strong light-matter interaction, in particular between localised plasmons and excitons in transition metal dichalcogenides (TMDCs) [1{3] has attracted great attention due to the strong oscillator strength in TMDCs [4]. The metal- TMDC interface provides a good platform to obtain strong coupling between excitons and plasmons [5]. However, this interface can a ect the exciton and trion properties of TMDCs [6]. While such systems have been studied, the e ect of the interface on the optical properties of the system remains an open problem. This work has studied the changes in optical properties of TMDC monolayers due to the presence of a metal interface, with the aim to create a metal nanoparticle- TMDC platform in which the optical and excitonic modes can potentially couple strongly. Focus was put on the changes to the spectral weight of excitons and trions in the TMDCs. To realise this work, mechanically exfoliated TMDC (molybdenum disul de(MoS2) or tungsten disul de(WS2)) was used together with a metal structure, of either chemically synthesised Silver (Ag) nano-plates or top-down fabricated gold (Au) nanodisks. Photoluminescence signals showed no signi cant trend in discrepancy under ambient conditions. However, a spectral shift was observed in re ection data depending on the substrate. In both photoluminescence and re ection a discrepancy was found between WS2-metal and WS2-dielectric system measurements. This contrast occurred in both ambient conditions and vacuum. The discrepancy became even clearer when the system was cooled to 77K and held at vacuum. The spectral weight was distributed among the neutral exciton and trion in the WS2-dielectric while the WS2-metal showed no trion. When investigating the scattering of light from Au nanodisks covered by 2D WS2 a red-shift was observed. In the case of 40 and 60 nm nanodisks a splitting in scattering spectra was also observed. This splitting can be attributed to a weak coupling between the exciton in TMDC and the plasmonic mode of the Au nanoparticle. However, more measurements are needed to con rm this result.
Keywords: Nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanovetenskap och nanoteknik; Nano Technology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nanoscience & Nanotechnology